Ability of Strategic Competence of Mathematically Proficiency in Completing Open Ended Mathematical Questions: Kemampuan Strategic Competence Of Mathematically Proficiency Dalam Menyelesaikan Soal Matematika Open Ended - eka filahanasari (International Journal of Technology Vocational Education and Training, 2020)
The purpose of this research is described strategic competence of mathematically proficiency’s students resolve a math problem using open-ended questons.The research was conducted in SMPN 5 Bungo .The kind of research qualitative descriptive, the data using test shaped about open-ended instrument of matter two variable system of linear equations and interviews. Data analysis done by reduction , presentation of data and verification or withdrawal of the conclusions .The result showed that students who were the subject of study has fulfilled all indicators strategic competence. Subject to the six indicators strategic understanding a situation and the competence of the problem , find kata-kata hal-hal key and ignoring the irrelevancy of the problem , presents a question it is mathematically in various forms , choose the presentation of suitable to help solve the problem , choose an effective method of settlement to resolve the problem and find a solution given from trouble .But not all the indicators look in pieces the subject , it is strengthened by the interview .So that all the indicators have been met by the subject.